Application of purple phototrophic bacteria in a biofilm photobioreactor for single cell protein production: Biofilm vs suspended growth. (15th August 2020) - Hülsen, Tim; Sander, Elisa Marx; Jensen, Paul D.; Batstone, Damien J.
Abstract: Single cell protein (SCP), has been proposed as alternative to effectively upgrade and recycle organics and nutrients from wastewater. Biomass recovery is a critical issue, and recovery as a biofilm is effective in comparison with sedimentation of suspended biomass. This study aims to determine the applicability of purple phototrophic bacteria (PPB) biofilm on infra-red irradiated, submerged surfaces for the treatment of pre-settled red meat processing wastewater, and SCP generation. PPB removed up to 66% of COD and 42% of TN and TP during batch operation with total areal productivities between 15 and 20 gVS m −2 d −1 achieved. More than 60% of the total biomass grew attached (as biofilm) with the remainder being suspended. The biofilm can be harvested at around 160 gTS L −1 with high protein (>96 g L −1 ) and low ash contents (>4.0% compared to >30% in the wastewater). The compositions of attached and suspended biomass differed significantly, where the suspended fraction resembled the wastewater composition (e.g. in terms of inert components). The PPB community was similar in the suspended and biofilm fractions while the biofilm had higher relative abundance of PPB representatives (57% vs 43%). A consistent product composition is highly relevant for the manufacturer and ultimately determines the value as feed, feed additive, or supplement. Highlights: Biofilm reactor could remove 66% COD and 42% nitrogen and phosphorus from meat processing wastewater. Up to 57% biomass grown was as a biofilm at ∼16% dry matter. Biofilm had a relatively high organic fraction and chemical consistency. Significant difference in microbial composition of biofilm vs suspended fractions.